(untitled) (Jurnal Ilmu Pendidikan dan Sains: Visioedusains, 2025)
Medicinal plants have been proven to contain active compounds that have been characterized as being able to prevent various diseases. Medicinal plants are still an alternative for many traditional communities in the treatment process. Local knowledge of medicinal plants by traditional communities is very important. However, currently most people prefer modern medicines. The purpose of this study was to determine the types of medicinal plants and how to process them in Mekar Bersatu Village. The population in this study, namely all types of medicinal plants in Mekar Bersatu Village and the samples used, namely the types of medicinal plants found in 5 hamlets in Mekar Besatu. Data were obtained through interviews and observations. Respondents were determined using the Purposive sampling technique. Medicinal plant data were analyzed using a qualitative descriptive method by summarizing the results of interviews and analyzing the types of medicinal plants and how to process them. The results showed that there were 30 types of medicinal plants in Mekar Bersatu Village. with the Spermatophyta plant group. A total of 6 plants came from the Zingiberaceae family. While the most common processing method is extracted and applied to the body.